Adaptation of homotopy-perturbation method for numeric–analytic solution of system of ODEs - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Elsevier, 2008)
A new reliable algorithm based on an adaptation of the standard Homotopy-Perturbation Method (HPM) is presented. The HPM is treated,for the first time, as an algorithm in a sequence of intervals (i.e., time step) for finding accurate approximate solutions of linear and nonlinear systems of ODEs. Numerical comparisons between the multistage Homotopy-Perturbation Method (MHPM) and the available exact solution and the classical fourth-order Runge–Kutta (RK4) method reveal that the new technique is a promising tool for linear and nonlinear systems of ODEs.